2012
DOI: 10.1038/ki.2012.106
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate and lower graft function reduce the seroresponse of kidney transplant recipients to pandemic H1N1 vaccination

Abstract: In late 2009 transplant organizations recommended that kidney recipients be vaccinated for pandemic H1N1 influenza (pH1N1); however, the vaccine efficacy was unknown. We had offered a monovalent non-adjuvanted pH1N1 vaccine to transplant recipients. Here we compared the pre- and post-vaccination seroresponses of 151 transplant recipients to that of 71 hemodialysis patients and 30 healthy controls. Baseline seroprotection was similar between groups but was significantly different at 1 month (44, 56, and 87%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 23 publications
6
48
1
1
Order By: Relevance
“…30 Reduced eGFR in kidney transplant recipients has also been associated with poor vaccine responsiveness. 31 These factors may in part explain why reduced eGFR was an important risk factor for severe infection in our study. 16 Mycophenolate use had previously been shown to be associated with increased risk of infection.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…30 Reduced eGFR in kidney transplant recipients has also been associated with poor vaccine responsiveness. 31 These factors may in part explain why reduced eGFR was an important risk factor for severe infection in our study. 16 Mycophenolate use had previously been shown to be associated with increased risk of infection.…”
Section: Discussionmentioning
confidence: 70%
“…For example, defective phagocytosis can be caused by uremic toxins, iron overload, and anemia of renal disease . Reduced eGFR in kidney transplant recipients has also been associated with poor vaccine responsiveness . These factors may in part explain why reduced eGFR was an important risk factor for severe infection in our study …”
Section: Discussionmentioning
confidence: 99%
“…Although patients had a significant increase in antibody levels initially, titers significantly declined by 3 months after liver transplant. Studies with influenza vaccine have also shown that humoral responses are greater in hemodialysis patients compared with transplant recipients [2,3].…”
Section: General Principles Of Immunization In Solid-organ Transplantmentioning
confidence: 97%
“…vaccine in the first year were immunized in the first 6 months after transplant. The use of mycophenolate mofetil (MMF) is also a well known factor leading to diminished immunogenicity [3,18]. A recent study found that higher doses of MMF of at least 2 g daily reduced the seroconversion rate of influenza vaccine [16 && ].…”
Section: Key Pointsmentioning
confidence: 99%
“…Influenza vaccination protected against influenza-like illness (50-70%) and against laboratory-confirmed influenza (70%) [120][121][122].…”
Section: Solid Organ Transplantation (Sot)mentioning
confidence: 99%